Antisense lncRNA CHROMR is linked to glioma patient survival - Širvinskas, Dovydas; Steponaitis, Giedrius; Stakaitis, Rytis; Tamašauskas, Arimantas; Vaitkienė, Paulina; Skiriutė, Daina (Frontiers in Molecular Biosciences, 2023)
Background: Natural non-coding antisense transcripts (ncNATs) are long non-coding RNAs (lncRNA) transcribed from the opposite strand of a separate protein coding or non-coding gene. As such, ncNATs can increase overlapping mRNA (and the coded protein) levels by stabilizing mRNA, absorbing inhibitory miRNAs and protecting the mRNA from degradation, or conversely decrease mRNA (or protein) levels by directing the mRNA towards degradation or inhibiting protein translation. Recently, growing numbers of ncNATs were shown to be dysregulated in cancerous cells, however, actual impact of ncNATs on cancer progression remains largely unknown. We therefore investigated gene expression levels of natural antisense lncRNA CHROMR (Cholesterol Induced Regulator of Metabolism RNA) and its sense protein coding gene PRKRA (Protein Activator of Interferon Induced Protein Kinase EIF2AK2) in gliomas. Next, we checked CHROMR effect on the survival of glioma patients. Methods: We performed RNA-seq on post-surgical tumor samples from 26 glioma patients, and normal brain tissue. Gene expression in TPM values were extracted for CHROMR and PRKRA genes. These data were validated using the TCGA and GTEx gene expression databases. Results: The gene expression level of ncNAT lncRNA CHROMR in glioma tissue was significantly higher compared to healthy brain tissue, while the expression of its sense counterpart protein coding PRKRA mRNA did not differ between glioma and healthy samples. Survival analysis showed lower survival rates in patients with low mRNA PRKRA/lncRNA CHROMR gene expression ratio compared to high ratio showing a link between lncRNA CHROMR and glioma patient survival prognosis. Conclusion: Here we show that elevated levels of lncRNA CHROMR (i.e., low ratio of mRNA PRKRA/lncRNA CHROMR) is associated with poor prognosis for glioma patients.